Prevalence of a Subtype in Iraqi Donations of National Blood Transfusion Center: Prevalensi Subtipe pada Donasi Pusat Transfusi Darah Nasional Irak - Yaqoob A. Wahid; Esraa K Shanyoor; Eman N. Naji; Marwah A Abduljabar (Academia Open, 2024)
General Background: The ABO blood group system is essential in blood transfusion, with subtypes of A and B groups influencing clinical outcomes. Specific Background: Subtypes A1 and A2 differ in the amount of antigen on red blood cells, impacting blood typing accuracy. Knowledge Gap: The prevalence of A2 and A2B subtypes in Iraqi donors remains underexplored, and their detection in routine screening can be challenging. Aims: This study aimed to determine the prevalence of A2 and A2B subtypes among Iraqi blood donors and evaluate the necessity of Anti-A1 reagent in accurate subtype identification. Results: In 2022, type O blood donors were the most prevalent, followed by B, A, and AB. A routine screening identified 0% A2 and 0.7% A2B subtypes, but 5% and 14.2% were A2B. Novelty: This study highlights the limitations of routine serological testing in detecting A subtypes, demonstrating that the use of Anti-A1 reagent significantly improves accuracy. Implications: Given the low rate of discrepancy between forward and reverse grouping, the Anti-A1 reagent should be routinely used for detecting A subtypes in clinical settings. Additionally, molecular techniques may be required to distinguish between rarer A subtypes such as A3, Ax, and Am. Highlights: ABO subtypes A1 and A2 are vital for precise blood transfusion typing. Routine tests miss A2; Anti-A1 reagent ensures accurate subtype detection. Molecular techniques help identify rarer subtypes like A3 and Ax. Keywords: ABO system, blood subtypes, Iraqi donors, Anti-A1 reagent, blood typing